A repository as ideas realization of open access for scientific publications: classification approaches - M. Yu. Rozhdestvenskaya (Библиосфера, 2015)
Russian institutional and thematic repositories are analyzed. The general and specific characteristics for systematization and classification of open access repositories are shown: the type (kind) of a repository, type and nature of an institution - owner of a repository, the nature of the data, access, protocol OAI-PMN, the metadata policy, software, the copyright, the opportunity for data self-archiving, the possibility of multiple search, category of user. Specific properties that distinguish them from other types of information retrieval systems are stressed. Different definitions of the term «repository» are analyzed and its new definition is proposed.